2016
DOI: 10.1155/2016/2392581
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Overlapping Fe/TiO2Prepared by Sol-Gel and Dip-Coating Process on CO2Reduction

Abstract: Fe-doped TiO2(Fe/TiO2) film photocatalyst was prepared by sol-gel and dip-coating process to extend its photoresponsivity to the visible spectrum. To promote the CO2reduction performance with the photocatalyst, some types of base materials used for coating Fe/TiO2, which were netlike glass fiber and Cu disc, were investigated. The characterization of prepared Fe/TiO2film coated on netlike glass fiber and Cu disc was analyzed by SEM and EPMA. In addition, the CO2reduction performance of Fe/TiO2film coated on ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…TiO2 as N-type semiconducting material has wide band gap with indirect energy band gap of 3.2 eV (anatase) and 3.02 eV (rutile) [6]. Several methods employed in preparation of TiO2 films include electron-beam evaporation [7,8], sputtering [9], sol-gel and dip coating, chemical vapour deposition [10] and spin-coating process [11][12][13]. Among the methods used, spin-coating offers advantages of low temperature processing, low cost, ease of coating large area and suitable for porous film preparation.…”
Section: Introductionmentioning
confidence: 99%
“…TiO2 as N-type semiconducting material has wide band gap with indirect energy band gap of 3.2 eV (anatase) and 3.02 eV (rutile) [6]. Several methods employed in preparation of TiO2 films include electron-beam evaporation [7,8], sputtering [9], sol-gel and dip coating, chemical vapour deposition [10] and spin-coating process [11][12][13]. Among the methods used, spin-coating offers advantages of low temperature processing, low cost, ease of coating large area and suitable for porous film preparation.…”
Section: Introductionmentioning
confidence: 99%
“…From these figures, it can be observed that the TiO 2 film with teeth-like shape was coated on a netlike glass fiber. It is also seen that TiO 2 film builds a bridge among several glass fibers like reported also in [38]. During firing process, the temperature profile of TiO 2 solution adhered on the [39].…”
Section: Co 2 Reduction Experimentmentioning
confidence: 69%
“…The Xe lamp can be fitted with a sharp cut filter to remove UV components of the light. With the filter, the wavelengths of light from the Xe lamp are ranged from 401 nm to 2000 nm [38]. The average light intensity of the Xe lamp on the photocatalyst without and with setting the sharp cut filter is 57.5 mW/cm 2 and 43.7 mW/cm 2 , respectively.…”
Section: Co 2 Reduction Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study has investigated overlapping two Fe/TiO 2 coated on netlike glass fiber in order to utilize the light more effectively as well as increase the amount of photocatalyst for CO 2 reduction. Though the effect of overlapping two Fe/TiO 2 coated on netlike glass fiber on CO 2 reduction performance with H 2 O was reported by Nishimura et al, 30 it was not investigated for CO 2 /H 2 /H 2 O. In addition, Nishimura et al 30 prepared Fe/TiO 2 by sol-gel dip-coating process only.…”
Section: Introductionmentioning
confidence: 99%